ANALISIS STRATEGI PEMULIHAN EKONOMI INDONESIA PASCA PANDEMI BERBASIS TRANSFORMASI DIGITAL - Maria Regina Nansi; Muhammad Yusuf; Anggun Septi N; Irfan Mustofa (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research aims to identify strategies and implementation results carried out by the Indonesian government to restore economic conditions during and especially after the pandemic. This type of research is included in quantitative-qualitative research with the qualitative variables in this research being the level of achievement of economic growth and economic recovery strategies, respectively. Primary data is data from interviews and secondary data is existing publication sources. The results show that the strategy implemented by the government, namely protecting, implementing PEN, capital participation, placing funds, and guarantee schemes has succeeded in restoring the condition of the Indonesian economy, especially entering the digitalization of the post-pandemic economy.